Ibadat korban : hukum & cara pengendaliannya - Brunei , Jabatan Mufti Kerajaan ([Bandar Seri Begawan] : State Mufti?s Office, Prime Minister?s Office, Brunei Darussalam, 2005)
Islamic principles and law governing the act of Qurban, a sacrifice by slaughtering animals such as lambs and goats, occur on Eid-ul-Adha festival; including fatwas by the state mufti of Brunei
In Malay, with some text in Arabic
Keywords: Islam -- Rituals; Sacrifice -- Islam